Analisis Manajemen Risiko Pada UMKM “Minuman Kecoklatan “ - Rahmawati, Siti; Ar Rachman, Hajar Chair; Karimah, Nur Rafidah (Universitas Serambi Mekkah, 2024)
Cocoa Beans are proven to be a source of antioxidants. One product that uses cocoa is a chocolate-based drink. preparation methods have developed in chocolate drinks. The aim of this research is to determine the antioxidant potential that can be maintained during the process of making chocolate drinks from cocoa powder using various preparation methods and to determine which can best maintain antioxidant activity. to use a Randomized Block Design with the factor Chocolate Drink Preparation Method (P) consisting of four treatments, which were repeated twice. chocolate drinks in capturing DPPH free radicals with supporting data, namely fat content in cocoa powder as well as total phenols and total flavonoids in cocoa powder and chocolate drinks. in the development of gluten free chocolate drink products as a strategy to diversify products and increase the competitiveness of micro, small and medium enterprises in MSMEs and the development of these products must be balanced with the manufacturer's ability to translate the level of consumer needs. The aim of determining the quality attributes of chocolate powder drinks is that producers that are acceptable and in accordance with consumer preferences.